2023
DOI: 10.1111/nph.18935
|View full text |Cite
|
Sign up to set email alerts
|

Re‐examining the evidence for the mother tree hypothesis – resource sharing among trees via ectomycorrhizal networks

Abstract: Seminal scientific papers positing that mycorrhizal fungal networks can distribute carbon (C) among plants have stimulated a popular narrative that overstory trees, or 'mother trees', support the growth of seedlings in this way. This narrative has far-reaching implications for our understanding of forest ecology and has been controversial in the scientific community. We review the current understanding of ectomycorrhizal C metabolism and observations on forest regeneration that make the mother tree narrative d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

3
14
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 29 publications
(17 citation statements)
references
References 56 publications
3
14
0
Order By: Relevance
“…Clearly, our data do not provide any support for these propositions. To the contrary, our results suggest that strong belowground competitive effects from adult trees suppress seedlings, in line with recent arguments questioning the validity of the mechanisms of common ectomycorrhiza networks as a resource transfer tool for adult trees to support seedlings (Henriksson et al 2023).…”
Section: Discussionsupporting
confidence: 89%
“…Clearly, our data do not provide any support for these propositions. To the contrary, our results suggest that strong belowground competitive effects from adult trees suppress seedlings, in line with recent arguments questioning the validity of the mechanisms of common ectomycorrhiza networks as a resource transfer tool for adult trees to support seedlings (Henriksson et al 2023).…”
Section: Discussionsupporting
confidence: 89%
“…It was impossible to separate the relative contributions made by these nonexclusive mechanisms using the methods described in this study. But there is no doubt that promoting carbon and nutrient transfer or uptake may still be a potentially important mechanism for invasive plants to promote seedling growth (Henriksson et al, 2023; Montesinos‐Navarro et al, 2019a; Simard et al, 2012).…”
Section: Discussionmentioning
confidence: 99%
“…Mycorrhizae, the ancient symbiosis between plant roots and fungi, have risen to the knowledge of the general public as altruistic conduits through which nutrients are moved around between forest trees and weak or young trees are nurtured by the old and strong ones [ 1 , 2 ]. While nutrient transfer in mycorrhizal systems has been studied isotopically for a relatively long time [ 3 , 4 ], and some studies have indicated the potential movement of nutrients between plants connected via the mycorrhizae, several scientists have recently raised concerns about this narrative [ 1 , 2 , 5 ]. Indeed, based on a recent meta-analysis [ 5 ], previous results show little evidence of this kind of nutrient transfer.…”
Section: Introductionmentioning
confidence: 99%
“…Indeed, based on a recent meta-analysis [ 5 ], previous results show little evidence of this kind of nutrient transfer. One major reason is that testing the nutrient transfer with isotopic methods does not enable the exclusion of alternative pathways, as the transfer pathway is only deduced based on various control treatments instead of being directly observed [ 2 , 5 ]. In this respect, conjugating the nutrients to intrinsically fluorescent quantum dots (QDs) for nutrient tracking in mycorrhiza-plant systems could be a viable option to exclude the alternative pathways and determine whether such transfer is taking place [ 5 ].…”
Section: Introductionmentioning
confidence: 99%